Islam dan Politik Identitas: Suatu Keharusan atau Pencegahan - Mutmainnah, Inayatul; Aderus, Andi; Hasyim, Jusniati (LPPM Universitas Madako Tolitoli, 2025)
Islamic identity politics serves a dual function in pluralistic societies: it can either enhance cohesion or intensify division. This study analyzes the dynamics of Islamic identity politics in Indonesia, emphasizing its capacity to promote Islamic ideals while acknowledging its divisive effects. This study employs qualitative approaches and case studies, including the 212 Movement, to elucidate the potential and challenges presented by identity politics. Research indicates that inclusive policies, intercultural conversation, and education are essential for converting identity politics into a catalyst for social cohesiveness. A multidisciplinary approach is essential to achieve equilibrium between religious aspirations and national integration, promoting democracy and global solidarity.